Faktor-Faktor yang Mempengaruhi Kejadian Gangguan Muskuloskeletal (MSDs) pada Petani Tebu di Indonesia: Tinjauan Pustaka - Nasser, Ghalib Abdul; Utomo, Muhammad Aditya; Winda Trijayanthi (Medula, 2025)
Musculoskeletal disorders (MSDs) are among the most common occupational health problems faced by workers in the agricultural sector, including sugarcane farmers in Indonesia. Excessive physical activity and performed without adequate ergonomic support make this group particularly vulnerable to musculoskeletal injuries. This study aims to synthesize determinant of MSDs among sugarcane farmers and to recommend targeted ergonomic strategies suitable for tropical agricultural environments through a literature review of scientific articles from relevant database. The findings indicate that MSDs are primarily influenced by repetitive work patterns, poor working posture, the use of non-ergonomic traditional tools, and adverse environmental conditions such as high temperatures and humidity. Additionally, psychosocial stress and limited access to ergonomic education and health facilities further exacerbate the condition. The review highlights the urgent need for comprehensive preventive strategies, including ergonomic interventions, occupational health education, improvements in working conditions, and psychosocial support. These efforts are essential to reduce the incidence of MSDs and enhance the occupational well-being of sugarcane farmers. The findings can guide policymakers in designing ergonomic-based agricultural health programs, especially among sugarcane farmers.